2021
DOI: 10.1177/1076029621999722
|View full text |Cite
|
Sign up to set email alerts
|

Serum Adenosine Deaminase as a Useful Marker to Estimate Coronary Artery Calcification in Type 2 Diabetes Mellitus Patients

Abstract: We investigated the association between serum adenosine deaminase and coronary artery calcification (CAC) in type 2 diabetes mellitus (T2DM) patients. The cross-sectional study included 459 patients with T2DM, the clinical and laboratory tests were performed, and all T2DM patients were separated into the 3 groups based on the tertile of serum adenosine deaminase levels. In the baseline data, the CAC score had statistically significant differences between the 3 groups (p < 0.001). Serum adenosine deaminase l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…In the present study, we observed that serum ADA levels were significantly positively correlated with CRP levels, ESR, Fg levels and D-dimer levels. Similar to our study, Yu et al ( 22 ) also found that serum ADA levels were positively correlated with CRP levels in patients with T2D. ADA is most abundantly expressed in lymphoid tissues and is indispensable for regulating the proliferation and differentiation of T lymphocytes and the maturation and function of monocytes and macrophages ( 23 ).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, we observed that serum ADA levels were significantly positively correlated with CRP levels, ESR, Fg levels and D-dimer levels. Similar to our study, Yu et al ( 22 ) also found that serum ADA levels were positively correlated with CRP levels in patients with T2D. ADA is most abundantly expressed in lymphoid tissues and is indispensable for regulating the proliferation and differentiation of T lymphocytes and the maturation and function of monocytes and macrophages ( 23 ).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, serum ADA levels were also found to be elevated in inflammatory diseases, such as ectopic pregnancy, gestational diabetes mellitus, preeclampsia, and inflammatory bowel disease ( 31 34 ). In addition, patients with increased cardiometabolic risks are always characterized by elevated serum ADA levels, and these cardiometabolic risks include higher BMI ( 35 ), increased TC ( 36 ), hypertension ( 16 ), atherosclerosis ( 13 ), thrombosis ( 14 ), coronary artery calcification ( 37 ) and T2D ( 38 ). Furthermore, in our previous studies and other previous studies, elevated serum ADA levels are not only involved in impaired pancreatic β-cell function in T2D ( 39 ) but also contribute to several diabetic complications, such as diabetic retinopathy ( 40 ), diabetic nephropathy ( 41 ), and prolonged heart QT interval in T2D ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of ADA is significantly increased in tissues rich in macrophage in a rat model of fecal peritonitis ( 24 ). Yu et al revealed that in patients with T2D, serum ADA levels were positively associated with C-reactive protein (CRP) and could be a useful marker to assess the severity of atherosclerosis ( 14 ). In our previous study, serum ADA levels were significantly associated with evaluation indexes of diabetic kidney disease (DKD), such as UACR, cystatin C and eGFR, and potentially were an important risk factor for DKD.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, elevated serum ADA levels in T2D may be associated with myocardial ischemia. Coincidentally, Yu et al have found that serum ADA levels are associated with the severity of atherosclerosis ( 14 ). A cross-sectional study of 501 patients with T2D exhibits that hyperglycemia and myocardial ischemia are important contributors to prolonged QTc ( 15 ).…”
Section: Introductionmentioning
confidence: 99%